Optimization of Cream Base and Hedonic Evaluation of Telon Cream with Variations in Essential Oil Composition - Marissa, Zahra; Mita, Soraya Ratnawulan; Kusumawulan, Cahya Khairani (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Telon cream was developed as an alternative to traditional telon oil for infants to lower the risk of skin irritation from high essential-oil content while retaining its characteristic warming effect. This study optimized the cream base using the Simplex Lattice Design (SLD) and evaluated the effect of different essential-oil compositions on physical stability and sensory acceptance, focusing on the warming sensation. The base was optimized by varying the ratio of Olivem® 1000 and Flocare™ SK 425 to achieve suitable viscosity, spreadability, and adhesiveness. The optimized base was used to prepare four telon-cream formulas containing cajuput, fennel, ginger, and lavender oils. Stability was assessed by organoleptic observation, pH, viscosity, and spreadability under three storage conditions for four weeks. A hedonic test with 30 caregivers evaluated color, texture, aroma, and warming sensation using a 5-point liking scale. The optimal base ratio (Olivem® 1000:Flocare™ SK 425 = 4:1) yielded a desirability value of 1,0. All formulas met pH (5,9–6,1), viscosity (38,000–46,000 mPa·s), and spreadability (5,0–5,4 cm) requirements and remained stable. Hedonic testing showed no significant differences in color (p-value = 0,939) or texture (p-value = 0,665); aroma showed a borderline difference (p-value = 0,060), whereas the warming sensation differed significantly (p-value = 0,010). Formula F4 (cajuput 0,4%, fennel 0,4%, ginger 0,1%, lavender 0,1%) achieved the highest warming-sensation score with a favorable aroma. The optimized telon cream demonstrated good stability and was well accepted by users. The warming sensation emerged as a key attribute influencing consumer preference for telon creams.